Genetic divergence in tropical anurans: deeper phylogeographic structure in forest specialists and in topographically complex regions - Rodriguez, Ariel; Boerner, Miriam; Pabijan, Maciej; Gehara, Marcelo; Haddad, Celio F. B. [UNESP]; Vences, Miguel (Springer, 2015)
Many tropical organisms show large genetic differences among populations, yet the prevalent drivers of the underlying divergence processes are incompletely understood. We explored the effect of several habitat and natural history features (body size, macrohabitat, microhabitat, reproduction site, climatic heterogeneity, and topography) on population genetic divergence in tropical amphibians, based on a data set of 2680 DNA sequences of the mitochondrial cytochrome b gene in 39 widely distributed frog species from Brazil, Central America, Cuba, and Madagascar. Generalized linear models were implemented in an information-theoretic framework to evaluate the effects of the six predictors on genetic divergence among populations, measured as spatially corrected pairwise distances. Results indicate that topographic complexity and macrohabitat preferences have a strong effect on population divergence with species specialized to forest habitat and/or from topographically complex regions showing higher phylogeographic structure. This relationship changed after accounting for phylogenetic relatedness among taxa rendering macrohabitat preferences as the most important feature shaping genetic divergence. The remaining predictors showed negligible effects on the observed genetic divergence. A similar analysis performed using the population-scaled mutation rate (I similar to) as response variable showed little effect of the predictors. Our results demonstrate greater evolutionary independence among populations of anurans from forested regions versus species from open habitats. This pattern may result from lower vagility and stringency in reproductive requirements of rainforest species. Conversely, open landscapes may offer ephemeral and unstable breeding sites suitable for vagile generalist species, resulting in reduced intraspecific divergence. Our results predict that, for a given period of time, there should be a higher chance of speciation in tropical anurans living in forests than in species adapted to open habitats.
Keywords: Amphibia; Anura; Phylogeography; Cytochrome b; Geographic distance; Population divergence; Madagascar; Brazil; Cuba; Central America